Teaching strategy: Strength and limitation of teaching strategies for nursing education via lecture and simulation - Mardiana, Mansor; Ayu Sulaini, Jusoh; Choon, Lim Chin (2017)
The purpose of this article is to discuss the strengths and limitations of two teaching strategies currently utilized in Diploma in Nursing, in Malaysia. The diploma was started in 1994 with a 3 years duration of study. It also requires certificates of qualification from the Malaysian Quality Agency (MQA) and the Malaysian Board of Nursing. Teaching strategies of individual teachers differ according to their teaching styles and generalized lesson plans, which include structures, instructional objectives, outlines of teaching and learning tactics, and other accessories needed to implement the strategies. A strategy does not necessarily follow a single track all the time, but changes according to the demands of the situations such as the age, level, needs, interests and abilities of the students. Thus, strategy is a method that is more comprehensive. It is directional in nature and refers to the goal oriented activities of the teacher. Hence, it resembles science rather than arts. Lecture and simulation methods are the best teaching strategies for nursing students in Malaysia. The lecture method allows clarification on difficult concepts, organizes thinking, and promotes problem solving attitudes, whereas simulation provides students with the opportunity for proper social, emotional and intellectual development. Moreover, students are highly motivated by educational simulation, for they enjoy the learning process while participating in it.